Budgetary Participation and Managerial Performance: Does Informality Matter? - Osee, Hanko (Archives of Business Research, 2025)
The budgetary participation and performance relationship has been studied mainly in the framework of big manufacturing companies with formal and structured existing budgets. This study aims at examining the same relationship within Small and Medium size companies where informal practices of budgeting have been identified by literature. An empirical analysis is carried out in Cameroon with companies selected based on the inexistence of a formal budget. Through a partial least square path analysis, the study concludes that budgetary participation does not directly affect managerial performance of small and medium size companies, but indirectly influences it through organisational commitment and perception of innovation. These two intervening variables partially mediate the relation between budgetary participation and managerial performance.